PERANAN KEPEMIMPINAN KEPALA DESA TERHADAP PENINGKATAN KESADARAN MASYARAKAT DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI DESA TOLOTOYON KECAMATAN PINOLOSIAN KABUPATEN BOLAANG MONGONDOW - Samin, Kartika (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The rural government continues to organize national tax system, the tax system in question is a reflection of a sense of justice, kesadarandan thorough in the sense that the tax levied on the tax object both large and small as well as to involve all levels of society. It is clear that basically the payment of taxes from the people intended for the prosperity of the people, or in other words from the people for the people. National development which resulted in the rapid development in various fields of life and public facilities ever increasing. As for the goal of this research was to determine how the leadership role of the village chief to increase public awareness in paying property tax. Through a state income tax policy can be enhanced, economic growth can be controlled, equitable distribution of income can also be implemented.The research method uses descriptive qualitative research explorative, primary data source is the village government apparatus numbering 12 people and the taxpayers of the UN which is determined in accordance with the number of sample as many as 13 people so the total sample used at the same informant in this study is the number 25 person. While the population in this study are all elements of society that are planted in areas of research Tolotoyon rural government efforts to encourage people to pay property taxes, government task forces village as a tax manager can actually provide motivation, socialize, coaching, counseling that how important it is for the state tax for the benefit of the people and the development of both infrastructure and superstructure areas , Awareness and obligations of society, especially in rural Tolotoyon felt still not all have a responsibility to pay taxes, administrative arrangement should be done well in order to motivate community members to achieve the goal of property tax payments, should be more intensive in providing socialization, counseling held , provide guidance to the public as taxpayers so that people can pay taxes on time.Key words: Leadership Rural Head, Tax build